2008
DOI: 10.1200/jco.2007.12.2382
|View full text |Cite
|
Sign up to set email alerts
|

Initial Patient Characteristics Can Predict Pattern and Risk of Relapse in Localized Rhabdomyosarcoma

Abstract: Initial patient and tumor characteristics predict pattern and risk of relapse and also correlate with postrelapse survival probabilities. In localized RMS, tumor-directed follow-up should focus on the primary site. Screening for metastatic relapse may not be necessary more than 4 years after diagnosis. The identification of subgroups with distinctive pattern and risk of relapse may be used to develop risk-adapted, tumor-directed guidance for detection of recurrent disease in localized RMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 27 publications
9
95
2
Order By: Relevance
“…Sharing the same classification would allow easier comparison between clinical presentation and behavior in adults and children. Finally, specific chemotherapy for A‐RMS and E‐RMS is an independent prognostic value in our study and others 2, 6, 7, 8, 9, 11, 14, 15, 38, 39, 40, 41, 43, 44, 45, 46, 47. North American and European pediatric groups have identified several risk factors (favorable location, IRSG stage, IRSG group, and age) to define the clinical group and deliver a regimen adapted to the risk group.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Sharing the same classification would allow easier comparison between clinical presentation and behavior in adults and children. Finally, specific chemotherapy for A‐RMS and E‐RMS is an independent prognostic value in our study and others 2, 6, 7, 8, 9, 11, 14, 15, 38, 39, 40, 41, 43, 44, 45, 46, 47. North American and European pediatric groups have identified several risk factors (favorable location, IRSG stage, IRSG group, and age) to define the clinical group and deliver a regimen adapted to the risk group.…”
Section: Discussionsupporting
confidence: 79%
“…Rhabdomyosarcoma (RMS) accounts for <3% of adult soft tissue sarcoma but is the most frequent soft tissue sarcoma histological subtype before age 10 and the 4th most prevalent cancer during childhood 1, 2, 3, 4. Five‐year overall survival (OS) of children has dramatically improved in the last 30 years based on the results of successive studies of large multinational collaborative trials dedicated to children.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In one recent single-institution study of high-risk neuroblastoma, time to first relapse was shown to influence length of survival 6 ; however, the relationship between initial tumor biologic and clinical risk factors was not extensively studied with regard to the length of second remission and survival after relapse. To gather additional information about the disease course after relapse, we queried the International Neuroblastoma Risk Group (INRG) database.…”
Section: Introductionmentioning
confidence: 99%
“…Similar study entry requirements exist within other large, international RMS consortia. 5,6 The primary purpose of staging evaluations is to identify the minority (16%) of newly diagnosed patients with distant metastases from the majority with only locoregional disease. This distinction has important implications for treatment assignment and prognosis.…”
Section: Introductionmentioning
confidence: 99%